Strategi Pelestarian Budaya Melalui Pembakuan Notasi Musik Kelintang Jolo di Muaro Jambi - Nelfira Dwina Amanda; Devi Harmita; Ayu Mardiana; Sri Minartih; Hebat Shidow Falah (EduInovasi: Journal of Basic Educational Studies, 2024)
This research aims to identify cultural preservation strategies through the standardization of Kelintang Jolo music notation in Muaro Jambi. The process skills used are ethnophysics-based qualitative research. This research uses a method that combines a qualitative approach with ethnographic and physics studies. The data collection techniques used were site survey, research instrument development, observation and documentation, interviews, data analysis and conclusion drawing, and evaluation. The results of this study indicate that Kelintang Jolo notation has an important role in preserving the traditional culture of Muaro Jambi which consists of (1) History of Kelintang Jolo. (2) The process of making Kelintang Jolo. (3) The concept of Ethnophysics in Kelintang Jolo. (4) Kelintang Jolo instrument. (5) Standardization of Music Notation. The implication of the research is expected support from various parties to maintain the sustainability of Kelintang Jolo music notation as a valuable cultural heritage. It is hoped that the results of this study can contribute to cultural preservation efforts through the standardization of traditional music notation in Indonesia.